Zirconium boride reinforced molybdenum alloy based on cold deformation regulation and preparation method thereof
Patent Information
- Application Number
- CN202611418769.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]为了解决上述现有钼合金制备工艺中存在的不足,本发明提供一种基于冷变形调控的硼化锆增强钼合金及其制备方法,通过在钼合金中引入高温陶瓷硼化锆,其能在烧结过程中与杂质氧发生反应净化基体,同时还能起到钉扎晶界、细化晶粒的效果,并且通过在室温下对合金进行动态塑性变形,引入高密度位错,结合退火工艺改善合金的组织结构,最终实现钼合金的强韧性协同匹配
1、本发明引入高温陶瓷硼化锆强化钼合金,在烧结过程中硼化锆可以吸收合金中的杂质氧,净化基体,生成的氧化锆颗粒还可以钉扎晶界和位错,引起细晶强化和弥散强化。
Smart Images

Figure CN122979798A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of alloy materials technology, specifically relating to a zirconium boride-reinforced molybdenum alloy based on cold deformation control and its preparation method. Background Technology
[0002] Molybdenum is a refractory metal with broad application prospects. Its characteristics include a high melting point, a low coefficient of thermal expansion, good compatibility with liquid metals such as Li / Na, and excellent electrical and thermal conductivity as well as corrosion resistance. Therefore, molybdenum alloys have wide application prospects in advanced manufacturing systems, aerospace propulsion components, and first-wall materials for nuclear fusion reactors. However, the intrinsic properties of molybdenum and the segregation of impurity elements (O, N) at the grain boundaries result in extremely low ductility of pure molybdenum at room temperature. Furthermore, it suffers from insufficient strength at high temperatures, susceptibility to recrystallization embrittlement, and potential embrittlement after irradiation, thus limiting its widespread application in various high-performance applications.
[0003] Currently, researchers mainly improve the strength and ductility of molybdenum by coupling second-phase dispersion strengthening with deformation strengthening. Second-phase dispersion strengthening introduces high-temperature ceramic second-phase particles, such as some carbide ceramics and oxide ceramics (ZrC, TiC, ZrO2, Y2O3), through methods such as ball milling and liquid-liquid doping. These particles pin grain boundaries and refine molybdenum grains during subsequent sintering, synergistically improving the strength and ductility of molybdenum alloys. In addition, the microstructure of molybdenum alloys is modified through high-temperature rotary forging and rolling. Hot working further improves the microstructure and properties of the alloy, increasing density and thus enhancing its mechanical properties. However, the aforementioned strengthening phases are difficult to directly interact with impurity elements in molybdenum alloys, and the grain refinement effect brought about by hot working is limited. Summary of the Invention
[0004] To address the shortcomings of existing molybdenum alloy preparation processes, this invention provides a zirconium boride-reinforced molybdenum alloy based on cold deformation control and its preparation method. By introducing high-temperature ceramic zirconium boride into the molybdenum alloy, it can react with impurity oxygen during sintering to purify the matrix, while also pinning grain boundaries and refining grains. Furthermore, by subjecting the alloy to dynamic plastic deformation at room temperature, high-density dislocations are introduced, and combined with annealing, the microstructure of the alloy is improved, ultimately achieving a synergistic match between strength and toughness in the molybdenum alloy.
[0005] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a method for preparing zirconium boride reinforced molybdenum alloy based on cold deformation control, comprising the following steps: S1. Raw material preparation: Molybdenum powder and zirconium boride powder are mixed to obtain a mixed powder; the purity of the molybdenum powder is ≥99 wt.%, and the particle size is 1µm~2µm; the purity of the zirconium boride powder is ≥99 wt.%, and the particle size is 0.2µm~0.5µm; the mass fraction of zirconium boride in the mixed powder is 0.7%; S2. Ball Milling and Sintering: Under the protection of a hydrogen-argon mixture (hydrogen volume fraction of 10%), the mixed powder obtained in S1 is ball-milled to obtain a ball-milled mixed powder. The ball-milling conditions are: ball-to-powder ratio of 13:1, rotation speed of 300 r / min, ball-milling time of 4 h, and grinding balls made of WC hard alloy with a particle size of 5 mm to 15 mm. Then, the ball-milled mixed powder is pre-pressed and sintered to obtain a sintered blank. The pre-pressing method is: the ball-milled mixed powder is placed in a graphite mold and pre-pressed for 5 min under a pressure of 25 MPa to obtain a pre-pressed mixed powder. The sintering method is: the pre-pressed mixed powder is sintered under a vacuum degree <10 -2 Two-stage vacuum hot pressing sintering was carried out under the condition of Pa. The procedure was as follows: first, the temperature was raised from room temperature to 1100℃ at a heating rate of 10℃ / min, and held at the temperature for 1h under a pressure of 50MPa; then, the temperature was raised to 1600℃ at a heating rate of 10℃ / min under a pressure of 50MPa, held for 0.5h, and then naturally cooled to room temperature. S3. Dynamic plastic deformation: The sintered billet obtained in S2 is subjected to multiple dynamic plastic deformations at room temperature, with each deformation amount being 5~20% and the total deformation amount being 50%~80%, to obtain a molybdenum alloy.
[0006] Preferably, it further includes: S4. Annealing: The molybdenum alloy obtained in S3 is annealed in an argon atmosphere; S5. Secondary dynamic plastic deformation: The annealed molybdenum alloy obtained in S4 is subjected to multiple passes of dynamic plastic deformation at room temperature, with a total deformation of 50% to 80% and a deformation of 5% to 20% per pass. S6. Final annealing: The molybdenum alloy obtained in S5 is annealed in an argon atmosphere; The annealing process is as follows: first, the temperature is raised from room temperature to 900~1300℃ at a heating rate of 5℃ / min, held for 0.5~2h, and then furnace cooled to room temperature.
[0007] Compared with the prior art, the present invention has the following significant technical effects: 1. This invention introduces high-temperature ceramic zirconium boride-strengthened molybdenum alloy. During the sintering process, zirconium boride can absorb impurity oxygen in the alloy, purify the matrix, and the generated zirconium oxide particles can also pin grain boundaries and dislocations, causing fine grain strengthening and dispersion strengthening.
[0008] 2. This invention introduces high-density dislocations into molybdenum alloys through dynamic plastic deformation at room temperature using Hopkinson bars, while simultaneously causing grain fibrillation. During subsequent annealing, these high-density dislocations transform into subgrain boundaries, refining the grains. These dislocations can also act as mobile dislocations, improving the alloy's plasticity through slip. The layered structure composed of fibrous grains and subgrains can hinder crack propagation, thereby increasing the alloy's strength, ultimately resulting in a molybdenum alloy with synergistic enhancement of strength and plasticity.
[0009] 3. By rationally controlling the amount of cold deformation and subsequent annealing process, this invention can obtain a very fine and uniform microstructure, which significantly improves the strength and plasticity of the material. The resulting molybdenum alloy has a yield strength of >600MPa and a tensile strength of >800MPa at room temperature. This effect is better than the level that can be achieved by relying solely on dynamic recrystallization or supplementary static recrystallization after hot deformation.
[0010] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments. Attached Figure Description
[0011] Figure 1 These are the inverse polarity (IPF) diagrams of the molybdenum alloys prepared in Examples 1 and 2 of the present invention: (a) the molybdenum alloy with dynamic plastic deformation obtained in Example 1, and (b) the molybdenum alloy with dynamic plastic deformation and annealing obtained in Example 2. Figure 2 These are grain boundary distribution (GB) diagrams of the molybdenum alloys prepared in Examples 1 and 2 of this invention. (a) The molybdenum alloy with dynamic plastic deformation obtained in Example 1, and (b) The molybdenum alloy with dynamic plastic deformation and annealing obtained in Example 2. Detailed Implementation
[0012] The molybdenum powder used in this invention was purchased from Chengdu Hongbo Industrial Co., Ltd., with a purity ≥99wt.% and a particle size of 1µm~2µm; the zirconium boride (ZrB2) powder was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with a purity ≥99wt.% and a particle size of 0.2µm~0.5µm.
[0013] Example 1
[0014] This embodiment describes a method for preparing zirconium boride-reinforced molybdenum alloy based on cold deformation control. The method is as follows: S1. Raw material preparation: Molybdenum powder and zirconium boride powder are mixed to obtain a mixed powder; the mass fraction of zirconium boride powder in the mixed powder is 0.7%.
[0015] S2, ball milling and sintering: Under the protection of a hydrogen-argon mixture (hydrogen volume fraction of 10%), the mixed powder obtained in S1 was placed in the cemented carbide ball mill jar of a planetary ball mill for ball milling to obtain the ball-milled mixed powder. The ball milling conditions were: ball-to-powder ratio of 13:1, rotation speed of 300 r / min, ball milling time of 4 h, and the grinding balls were cemented carbide balls made of WC material, which were mixed from cemented carbide balls with particle sizes of 5 mm, 8 mm, 10 mm, 12 mm and 15 mm respectively. Then, the ball-milled mixed powder is placed into a graphite mold and pre-pressed for 5 minutes under a pressure of 25 MPa to obtain the pre-pressed mixed powder. The pre-compressed mixed powder is then subjected to a vacuum degree <10 -2 Two-stage vacuum hot pressing sintering is carried out under the condition of Pa to obtain sintered blanks; the procedure of the two-stage vacuum hot pressing sintering is as follows: first, the temperature is raised from room temperature to 1100℃ at a heating rate of 10℃ / min, and held at 50MPa for 1h; then, under constant pressure, the temperature is raised to 1600℃ at a heating rate of 10℃ / min, held for 0.5h, and then naturally cooled to room temperature.
[0016] S3, Dynamic Plastic Deformation: The sintered billet obtained in S2 was subjected to multiple dynamic plastic deformations at room temperature using a Hopkinson bar, with each pass involving a deformation amount of 5% to 20%, and the total cumulative deformation amount being 70%, to obtain a molybdenum alloy.
[0017] Example 2
[0018] This embodiment describes a method for preparing zirconium boride-reinforced molybdenum alloy based on cold deformation control. The method is as follows: S1. Raw material preparation: Molybdenum powder and zirconium boride powder are mixed to obtain a mixed powder; the mass fraction of zirconium boride powder in the mixed powder is 0.7%.
[0019] S2, ball milling and sintering: Under the protection of a hydrogen-argon mixture (hydrogen volume fraction of 10%), the mixed powder obtained in S1 was placed in the cemented carbide ball mill jar of a planetary ball mill for ball milling to obtain the ball-milled mixed powder. The ball milling conditions were as follows: ball-to-powder ratio of 13:1, rotation speed of 300 r / min, ball milling time of 4 h, and the grinding balls were cemented carbide balls made of WC material, which were mixed from cemented carbide balls with particle sizes of 5 mm, 8 mm, 10 mm, 12 mm and 15 mm respectively. Then, the ball-milled mixed powder is placed into a graphite mold and pre-pressed for 5 minutes under a pressure of 25 MPa to obtain the pre-pressed mixed powder. The pre-compressed mixed powder is then subjected to a vacuum degree <10 -2Two-stage vacuum hot pressing sintering is carried out under the condition of Pa to obtain sintered blanks; the procedure of the two-stage vacuum hot pressing sintering is as follows: first, the temperature is raised from room temperature to 1100℃ at a heating rate of 10℃ / min, and held at 50MPa for 1h; then, under constant pressure, the temperature is raised to 1600℃ at a heating rate of 10℃ / min, held for 0.5h, and then naturally cooled to room temperature.
[0020] S3, Dynamic Plastic Deformation: The sintered billet obtained in S2 was subjected to multiple dynamic plastic deformations at room temperature using a Hopkinson bar, with each pass involving a deformation amount of 5% to 10%, and the total cumulative deformation amount being 70%, to obtain a molybdenum alloy block.
[0021] S4, Final Annealing: The molybdenum alloy block obtained in S3 was annealed in an argon atmosphere, with the temperature increased to 1300℃ at a heating rate of 5℃ / min, and annealed for 1 hour. After holding at that temperature, the furnace was cooled to room temperature to obtain the molybdenum alloy.
[0022] Example 3
[0023] This embodiment describes a method for preparing zirconium boride-reinforced molybdenum alloy based on cold deformation control. The method is as follows: S1. Raw material preparation: Molybdenum powder and zirconium boride powder are mixed to obtain a mixed powder; the mass fraction of zirconium boride powder in the mixed powder is 0.7%.
[0024] S2, ball milling and sintering: Under the protection of a hydrogen-argon mixture (hydrogen volume fraction of 10%), the mixed powder obtained in S1 was placed in the cemented carbide ball mill jar of a planetary ball mill for ball milling to obtain the ball-milled mixed powder. The ball milling conditions were as follows: ball-to-powder ratio of 13:1, rotation speed of 300 r / min, ball milling time of 4 h, and the grinding balls were cemented carbide balls made of WC material, which were mixed from cemented carbide balls with particle sizes of 5 mm, 8 mm, 10 mm, 12 mm and 15 mm respectively. Then, the ball-milled mixed powder is placed into a graphite mold and pre-pressed for 5 minutes under a pressure of 25 MPa to obtain the pre-pressed mixed powder. The pre-compressed mixed powder is then subjected to a vacuum degree <10 -2 Two-stage vacuum hot pressing sintering is carried out under the condition of Pa to obtain sintered blanks; the procedure of the two-stage vacuum hot pressing sintering is as follows: first, the temperature is raised from room temperature to 1100℃ at a heating rate of 10℃ / min, and held at 50MPa for 1h; then, under constant pressure, the temperature is raised to 1600℃ at a heating rate of 10℃ / min, held for 0.5h, and then naturally cooled to room temperature.
[0025] S3, Dynamic Plastic Deformation: The sintered billet obtained in S2 was subjected to multiple dynamic plastic deformations at room temperature using a Hopkinson bar, with each pass involving a deformation amount of 5% to 10%, and the total cumulative deformation amount being 50%, to obtain molybdenum alloy block 1.
[0026] S4, Intermediate Annealing: The molybdenum alloy block 1 obtained in S3 was subjected to intermediate annealing in an argon atmosphere. The temperature was increased to 900℃ at a heating rate of 5℃ / min, and annealed for 1 hour. After holding at the temperature, the furnace was cooled to room temperature to obtain molybdenum alloy block 2.
[0027] S5, Secondary Dynamic Plastic Deformation: The molybdenum alloy block 2 obtained in S4 is subjected to multiple dynamic plastic deformations at room temperature, with each deformation amount being 5%~10%, and the total cumulative deformation amount being 70%, to obtain the molybdenum alloy block 3.
[0028] S6, Final Annealing: The molybdenum alloy block 3 obtained in S5 was subjected to final annealing in an argon atmosphere. The temperature was increased to 1100℃ at a heating rate of 5℃ / min and annealed for 1 hour. After holding at this temperature, the furnace was cooled to room temperature to obtain the molybdenum alloy.
[0029] Example 4
[0030] This embodiment describes a method for preparing zirconium boride-reinforced molybdenum alloy based on cold deformation control. The method is as follows: S1. Raw material preparation: Molybdenum powder and zirconium boride powder are mixed to obtain a mixed powder; the mass fraction of zirconium boride powder in the mixed powder is 0.7%.
[0031] S2, ball milling and sintering: Under the protection of a hydrogen-argon mixture (hydrogen volume fraction of 10%), the mixed powder obtained in S1 was placed in the cemented carbide ball mill jar of a planetary ball mill for ball milling to obtain the ball-milled mixed powder. The ball milling conditions were as follows: ball-to-powder ratio of 13:1, rotation speed of 300 r / min, ball milling time of 4 h, and the grinding balls were cemented carbide balls made of WC material, which were mixed from cemented carbide balls with particle sizes of 5 mm, 8 mm, 10 mm, 12 mm and 15 mm respectively. Then, the ball-milled mixed powder is placed into a graphite mold and pre-pressed for 5 minutes under a pressure of 25 MPa to obtain the pre-pressed mixed powder. The pre-compressed mixed powder is then subjected to a vacuum degree <10 -2Two-stage vacuum hot pressing sintering is carried out under the condition of Pa to obtain sintered blanks; the procedure of the two-stage vacuum hot pressing sintering is as follows: first, the temperature is raised from room temperature to 1100℃ at a heating rate of 10℃ / min, and held at 50MPa for 1h; then, under constant pressure, the temperature is raised to 1600℃ at a heating rate of 10℃ / min, held for 0.5h, and then naturally cooled to room temperature.
[0032] S3, Dynamic Plastic Deformation: The sintered billet obtained in S2 was subjected to multiple dynamic plastic deformations at room temperature using a Hopkinson bar, with each pass involving a deformation amount of 5% to 10%, and the total cumulative deformation amount being 50%, to obtain molybdenum alloy block 1.
[0033] S4, Intermediate Annealing: The molybdenum alloy block 1 obtained in S3 was subjected to intermediate annealing in an argon atmosphere. The temperature was increased to 900℃ at a heating rate of 5℃ / min, and annealed for 1 hour. After holding at that temperature, the furnace was cooled to room temperature to obtain molybdenum alloy block 2. S5, Secondary Dynamic Plastic Deformation: The molybdenum alloy block 2 obtained in S4 is subjected to multiple dynamic plastic deformations at room temperature, with each deformation amount being 5%~10%, and the total cumulative deformation amount being 70%, to obtain the molybdenum alloy block 3.
[0034] S6, Final Annealing: The molybdenum alloy block 3 obtained in S5 was subjected to final annealing in an argon atmosphere. The temperature was increased to 1300℃ at a heating rate of 5℃ / min and annealed for 1 hour. After holding at this temperature, the furnace was cooled to room temperature to obtain the molybdenum alloy.
[0035] The molybdenum alloys prepared in Examples 1-4 were subjected to room temperature tensile tests after grinding and polishing.
[0036] Figure 1 These are the inverse polarity (IPF) diagrams of the molybdenum alloys prepared in Examples 1 and 2. (a) The molybdenum alloy with dynamic plastic deformation obtained in Example 1, and (b) The molybdenum alloy with dynamic plastic deformation and annealing obtained in Example 2. The two show significantly different morphologies: the molybdenum alloy with dynamic plastic deformation is mainly composed of fibrous grains, while after high-temperature annealing, the grain morphology is mainly composed of equiaxed grains and the structure is uniform.
[0037] Figure 2 These are grain boundary distribution (GB) diagrams of the molybdenum alloys prepared in Examples 1 and 2. (a) The molybdenum alloy with dynamic plastic deformation obtained in Example 1, and (b) The molybdenum alloy with dynamic plastic deformation and annealing obtained in Example 2. It can be seen that after dynamic plastic deformation, many substructures are generated inside the grains of the alloy; after annealing, the internal substructures disappear, and many fine equiaxed crystals appear at the grain boundaries.
[0038] The above results indicate that dynamic plastic deformation at room temperature can introduce high-density dislocations into molybdenum alloys, while simultaneously causing grain fibrosis. The layered structure composed of fibrous grains and subgrains can hinder crack propagation, thereby improving the alloy strength. Furthermore, after high-temperature annealing, Example 2 exhibits a fine, uniform, and nearly equiaxed grain structure with a relatively dispersed grain orientation. No obvious abnormal grain growth was observed. The more uniform structure also helps reduce local stress concentration and property anisotropy, thus contributing to a good strength-plasticity balance.
[0039] Based on the above analysis, dynamic plastic deformation and annealing can significantly change the microstructure of the material. In order to further verify the influence of dynamic plastic deformation and annealing process on the mechanical properties of the alloy, the mechanical properties of the molybdenum alloys prepared in Examples 1 to 4 were tested, and the results are shown in Table 1.
[0040] Table 1. Performance test results of zirconium boride-strengthened molybdenum alloy
[0041] As shown in Table 1, compared with pure molybdenum and other molybdenum alloys, the molybdenum alloy prepared by this invention can be deformed at room temperature and achieves high strength, with a yield strength >600MPa and a tensile strength >800MPa at room temperature, and exhibits a good strength-ductility balance. This invention first introduces zirconium boride into molybdenum-based materials, utilizing the oxygen-absorbing properties of zirconium boride at high temperatures to purify the matrix while simultaneously generating zirconium oxide pinning grain boundaries and refining the grains. Subsequently, by combining room-temperature dynamic plastic deformation, intermediate annealing, and final annealing processes, the microstructure of the alloy is controlled. Ultimately, this process integrates grain refinement strengthening, dispersion strengthening, and dislocation strengthening. The resulting molybdenum alloy exhibits a yield strength >600 MPa at room temperature and a tensile strength >800 MPa at room temperature, with a good strength-plasticity match, providing a new approach for selecting materials for the first wall structure of nuclear fusion reactors.
[0042] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the inventive essence shall still fall within the protection scope of the present invention.
Claims
1. A method for preparing zirconium boride-reinforced molybdenum alloy based on cold deformation control, characterized in that, Includes the following steps: S1. Raw material preparation: Mix molybdenum powder and zirconium boride powder to obtain a mixed powder; S2, ball milling and sintering: Under the protection of a hydrogen-argon mixture, the mixed powder obtained in S1 is ball milled to obtain ball-milled mixed powder; then the ball-milled mixed powder is pre-pressed and sintered to obtain sintered blanks; S3. Dynamic plastic deformation: The sintered billet obtained in S2 is subjected to multiple dynamic plastic deformations at room temperature, with a total deformation of 50% to 80%, to obtain a molybdenum alloy.
2. The method according to claim 1, characterized in that, The molybdenum powder in S1 has a purity ≥99 wt.% and a particle size of 1µm~2µm; the zirconium boride powder has a purity ≥99 wt.% and a particle size of 0.2µm~0.5µm; the mass fraction of zirconium boride in the mixed powder is 0.7%.
3. The method according to claim 1, characterized in that, The hydrogen volume fraction in the hydrogen-argon mixture described in S2 is 10%.
4. The method according to claim 1, characterized in that, The ball milling conditions described in S2 are: a ball-to-material ratio of 13:1, a rotation speed of 300 r / min, a milling time of 4 h, and grinding balls made of WC cemented carbide with a particle size of 5 mm to 15 mm.
5. The method according to claim 1, characterized in that, The pre-compression method described in S2 is as follows: the ball-milled mixed powder is placed into a graphite mold and pre-compressed for 5 minutes under a pressure of 25 MPa to obtain the pre-compressed mixed powder; The sintering method described in S2 is as follows: the pre-pressed mixed powder is sintered under a vacuum degree <10 -2 The two-stage vacuum hot pressing sintering was carried out under the condition of Pa. The procedure was as follows: first, the temperature was raised from room temperature to 1100℃ at a heating rate of 10℃ / min, and held at the temperature for 1h under a pressure of 50MPa; then, the temperature was raised to 1600℃ at a heating rate of 10℃ / min under a pressure of 50MPa, held for 0.5h, and then naturally cooled to room temperature.
6. The method according to claim 1, characterized in that, The total deformation amount of the multi-pass dynamic plastic deformation is 50%~80%, and the deformation amount of each pass is 5~20%.
7. The method according to claim 1, characterized in that, Also includes: S4. Annealing: The molybdenum alloy obtained in S3 is annealed in an argon atmosphere.
8. The method according to claim 7, characterized in that, Also includes: S5. Secondary dynamic plastic deformation: The annealed molybdenum alloy obtained in S4 is subjected to multiple passes of dynamic plastic deformation at room temperature, with a total deformation of 50% to 80% and a deformation of 5% to 20% per pass. S6. Final annealing: The molybdenum alloy obtained in S5 is annealed in an argon atmosphere.
9. The method according to claim 7 or 8, characterized in that, The annealing process is as follows: first, the temperature is raised from room temperature to 900~1300℃ at a heating rate of 5℃ / min, held for 0.5~2h, and then furnace cooled to room temperature.
10. The method according to claim 1, characterized in that, The resulting molybdenum alloy has a yield strength >600MPa and a tensile strength >800MPa at room temperature.